2012
DOI: 10.1108/14757701211279178
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the type and number of internal control weaknesses and their remediation on audit fees

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…This is also because the previous year's figures are restated in the next accounting period. Research by Keane et al (2013) showed that the company will reveal the same material weaknesses in the previous and current years.…”
Section: Influence Of Findings Of Internal Control Weaknesses In the mentioning
confidence: 99%
See 1 more Smart Citation
“…This is also because the previous year's figures are restated in the next accounting period. Research by Keane et al (2013) showed that the company will reveal the same material weaknesses in the previous and current years.…”
Section: Influence Of Findings Of Internal Control Weaknesses In the mentioning
confidence: 99%
“…Mulyani & Suryawati, 2011). ResearchKeane et al (2013) stated the audit findings of the previous year positively and significantly influence the same findings in the audit year. Yamin & Sutaryo (2014) stated that the findings of internal control weaknesses in the previous year positively affect the weaknesses of internal control of local governments H5: Findings of the weakness of internal control in the previous year positively influences the weaknesses of internal control of the local governments.…”
mentioning
confidence: 98%
“…Public opinion on corporate misconduct not only damages the social image of the company and the manager, but also urges other institutions to strengthen board supervision. Prior literature shows that disclosing ICW causes negative consequences in falling stock price (Hammersley et al, 2008), increasing capital cost (Ashbaugh-Skaife et al, 2009), raising audit fees (Keane, Elder, & Albring, 2012) and poor performance (Esmaeili & Sharigabadi, 2015).…”
Section: Internal Control Weakness and Ceo Media Exposurementioning
confidence: 99%
“…Based on resource dependency theory that stresses entity's economic needs for internal control over administering federal funding, they select a sample of nonprofit hospitals subject to the Single Audit Act in the United States, from 2001 to 2008. Their results show that hospitals that had audit committees and also employed Big 4 auditors were associated with better internal control quality [4].…”
Section: Introductionmentioning
confidence: 98%